A Comparative Study of Growth and Yield of some Hybrids of Squash Cucurbita Pepo L. When Grown in Different Agricultural Densities - شيخ سليمان, نصر; طحان, وسام (Latakia University Journal -Biological Sciences Series, 2020)
The study was conducted in the village of Skoubine region /North of Lattakia/ in the spring season of 2019, with the aim of studying the effect of plant density on the growth and productivity of some squash hybrids. The experiment included the evaluation of three hybrids of squash, which is (French hybrid Précoce Maraîchère, hybrid Maram F1, hybrid Zainab F1) planted in six agricultural densities (2.7, 2.4, 2, 1.8, 1.6, 1.4) plants/m2 to study the indicators of vegetative and fruiting growth and productivity. According to a randomized complete block design, with four replicates per treatment, and at rate of ten plants per replicate. The results showed that the hybrid plants of Zainab exceeded significant differences over the other hybrids in all studied treatments and gave the treatment with plant density ( 1.4 ) plants/m2 the highest number of leaves reached ( 26 ) sheets/ plant while the number was the leaves for the same treatment are in Maram hybrid ( 24 ) leaves/ plant and in the French hybrid ( 22 ) leaves/ plant. Also, the hybrid Zainab was significantly superior to the Maram hybrid and the Précoce Maraîchère hybrid with the leaf surface area in all studied treatments for plant densities, and the treatment with plant density (1.4) plants/m2 gave the largest leaves surface reached ( 35636 ) cm2/ plant, while the treatment with plant density (2.7) plants/m2 gave the lowest leaves flat for the same hybrid amounted to (21367) cm2/ plant and in the French hybrid the lowest leaves flat reached (15654) cm2/ plant at the plant density (2.7) plants/m2,It was also found that the sexual ratio was high for the three hybrids at high plant densities and decreased to the lowest percentage in low plant densities, and it reached (30.55)% for the Maram hybrid, (28.37)% for the Zeinab hybrid and (28.89) % for the precious hybrid when planting at plant density (1.4) plants/m2. The treatment with low plant density (1.4) plants/m2 gave the highest rate of early production for all the studied treatments.